2009
DOI: 10.1002/acp.1598
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interleaved practice

Abstract: Previous research shows that interleaving rather than blocking practice of different skills (e.g. abcbcacab instead of aaabbbccc) usually improves subsequent test performance. Yet interleaving, but not blocking, ensures that practice of any particular skill is distributed, or spaced, because any two opportunities to practice the same task are not consecutive. Hence, because spaced practice typically improves test performance, the previously observed test benefits of interleaving may be due to spacing rather th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
185
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(221 citation statements)
references
References 25 publications
(24 reference statements)
17
185
1
2
Order By: Relevance
“…This implication may extend well beyond visual categories of the type employed in the present studies. Taylor and Rohrer (2010), for example, asked students to learn four kinds of mathematics problems using a task that could be categorized as requiring inductive learning, because participants never saw the same problem twice during the learning phase. Taylor and Rohrer found that interleaving enhanced learning-as measured by the ability to solve new examples of each type of problem on a delayed test-even when the amount of spacing had been the same in the interleaved and blocked conditions.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implication may extend well beyond visual categories of the type employed in the present studies. Taylor and Rohrer (2010), for example, asked students to learn four kinds of mathematics problems using a task that could be categorized as requiring inductive learning, because participants never saw the same problem twice during the learning phase. Taylor and Rohrer found that interleaving enhanced learning-as measured by the ability to solve new examples of each type of problem on a delayed test-even when the amount of spacing had been the same in the interleaved and blocked conditions.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…There may be situations in which it is advantageous to block such learning trials, as has been demonstrated using artificial laboratory tasks, particularly when it is difficult to discern similarities among the exemplars of a category. In the case of naturalistic categories, however, the data thus far are fairly unanimous in demonstrating the benefits of interleaving over blocking (Kang & Pashler, 2012;Kornell & Bjork, 2008;Kornell et al, 2010;Taylor & Rohrer, 2010;Wahlheim et al, 2011;Zulkiply & Burt, in press;Zulkiply et al, 2012).…”
Section: Concluding Commentmentioning
confidence: 99%
“…The benefits of using multiple examples rather than only one example in mathematics education, in regard to student learning, have been argued by several scholars (e.g., (Hatala et al 2003;Kornell and Bjork 2008;Rohrer and Pashler 2010;Schmidt and Bjork 1992;Taylor and Rohrer 2010). When different types of tasks or examples are mixed, the learners are forced to distinguish between them and thus get better at making sense of novel tasks and examples.…”
Section: Variation and Exemplificationmentioning
confidence: 99%
“…Other studies have reported benefits of interleaving on the learning of geometric concepts (e.g., Taylor & Rohrer, 2010) and algebraic rules (e.g., Mayfield & Chase, 2002). A small but growing number of studies has also reported benefits of interleaving for other types of cognitive and motor tasks as well (for reviews, see Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013;Rohrer, 2012).…”
Section: Abstract Interleaving Pronunciation Learning Discriminatmentioning
confidence: 99%
“…Students worked through practice problems in an order that was either blocked by type of figure (i.e., all problems pertaining to one type of figure were finished before the student moved on to the next type of figure) or interleaved such that the same problems appeared in an order that was shuffled and unpredictable. On a later test requiring students to calculate the volumes for similar types of figures, students scored higher if they had learned the information through interleaving, as compared with blocking.Other studies have reported benefits of interleaving on the learning of geometric concepts (e.g., Taylor & Rohrer, 2010) and algebraic rules (e.g., Mayfield & Chase, 2002). A small but growing number of studies has also reported benefits of interleaving for other types of cognitive and motor tasks as well (for reviews, see Dunlosky, Rawson, Marsh, Nathan, & Willingham, 2013;Rohrer, 2012).…”
mentioning
confidence: 99%